2020
DOI: 10.1101/2020.09.20.20198143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resuming assisted reproduction services during COVID-19 Pandemic: An Indian experience

Abstract: Purpose: The pandemic of COVID-19 has affected many countries and medical services including assisted reproductive treatment (ART) have been hampered. The purpose of the study was to assess the preparedness of ART clinics and staff to resume services and patients reasons to initiate treatment and key performance indicators (KPIs) of ART labs during pandemic. Methods: Semi-descriptive report of two private in-vitro fertilization (IVF) clinics in Maharashtra, India, when COVID-19 testing for asymptomatic people… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Considering the high rate of human-tohuman transmission and viral shedding from both symptomatic and asymptomatic individuals [39], high asymptomatic to symptomatic patient ratio [40] and ability of the viruses to survive on inanimate objects for extended periods and at sub-zero temperatures [41,42], the clinics offering assisted reproduction services are at risk of spreading COVID-19 [43]. With the resumption of services for assisted reproduction in many parts of the world [44,45], the clinics must be aware of the risks that the virus poses on gametes and early embryos. Indeed, we and others have demonstrated that ACE2 is expressed in the different types of embryonic and trophectodermal cells [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high rate of human-tohuman transmission and viral shedding from both symptomatic and asymptomatic individuals [39], high asymptomatic to symptomatic patient ratio [40] and ability of the viruses to survive on inanimate objects for extended periods and at sub-zero temperatures [41,42], the clinics offering assisted reproduction services are at risk of spreading COVID-19 [43]. With the resumption of services for assisted reproduction in many parts of the world [44,45], the clinics must be aware of the risks that the virus poses on gametes and early embryos. Indeed, we and others have demonstrated that ACE2 is expressed in the different types of embryonic and trophectodermal cells [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%